Brains online: structural and functional correlates of habitual Internet use. (24th February 2014) - Kühn, Simone; Gallinat, Jürgen
Abstract In the past decades, the Internet has become one of the most important tools to gather information and communicate with other people. Excessive use is a growing concern of health practitioners. Based on the assumption that excessive Internet use bears resemblance with addictive behaviour, we hypothesized alterations of the fronto‐striatal network in frequent users. On magnetic resonance imaging scans of 62 healthy male adults, we computed voxel‐based morphometry to identify grey matter (GM) correlates of excessive Internet use, assessed by means of the Internet Addiction Test (IAT) and functional connectivity analysis and amplitude of low‐frequency fluctuation (ALFF) measures on resting state data to explore the functional networks associated with structural alterations. We found a significant negative association between the IAT score and right frontal pole GM volume (P < 0.001, family wise error corrected). Functional connectivity of right frontal pole to left ventral striatum was positively associated with higher IAT scores. Furthermore, the IAT score was positively correlated to ALFF in bilateral ventral striatum. The alterations in the fronto‐striatal circuitry associated with growing IAT scores could reflect a reduction of top‐down modulation of prefrontal areas, in particular, the ability to maintain long‐term goals in face of distraction. The higher activation of ventral striatum at rest may indicate a constant activation in the context of a diminished prefrontal control. The results demonstrate that excessive Internet use may be driven by neuronal circuits relevant for addictive behaviour.